A Rapid Molecular Assay for Detecting the Mediterranean Fanworm Sabella spallanzanii Trialed by Non-Scientist Users - Zirngibl, Martin; von Ammon, Ulla; Pochon, Xavier; Zaiko, Anastasija (Frontiers in Marine Science, 2022)
The invasive Mediterranean fanworm Sabella spallanzanii (Gmelin, 1791) is a notifiable organism under New Zealand’s Biosecurity Act and is recognized as a marine pest of particular concern, that must be reported to the Ministry for Primary Industries (MPI), New Zealand. Since its first detection in 2008, great effort and financial resources are put into surveillance and removal of individuals to contain population growth and spread. Sensitive molecular detection techniques gain great interest and are being increasingly tested for the fanworm detection in marine high-risk sites (i.e., ports and marinas) around New Zealand. However, conventional molecular detection via PCR assays from environmental DNA (eDNA) samples requires specific laboratory resources and technical expertise. This restricts the wider applicability of this approach by biosecurity practitioners or communities willing to be engaged in biosecurity surveillance. To provide end-users with a fast, easy and highly specific way to detect S. spallanzanii directly at the site of interest, a species-specific recombinase polymerase amplification (RPA) assay was designed to be read-out with lateral flow strips (RPA-LF). The RPA generates amplification within 20 minutes at 37-39°C, with a detection limit of 10 pg of the target DNA and was matching the detection limit of digital droplet PCR (ddPCR) when performed on eDNA samples. A simplified visual protocol for non-scientist users of the assay was developed and improved through independent trials with different end-user groups. The assay applicability was verified in a final validation trial with participants without scientific background resulting in 50 percent of the participants successfully detecting S. spallanzanii. Participants rated the ease of use and performance and read-out mostly as easy-to-very easy with overall positive written feedback on its usability for citizen science applications.